Comparative Study Between Fixed Solar Panel and Sun Tracking Solar Panel - THAXAIYA, Vongphone; PANTHONGSY, Phosy; THONGPHANH, Phoutsavanh; DITTAPHONG, Xaysamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Electricity is one of the necessary things to improve the quality of life. However, many remote rural areas and villages located on the mountain have no electricity supply, leading to a difficult living-life. So that, looking for an alternative energy source is essential. The objective of this paper is to examine the sufficient and stable energy source for villagers who live in Hua Kung Village, Sam Nua District, Hua Phan Province. The solar energy harvesting is focused. This study aims to compare the capacity of solar energy supply. In which the instrument used to collect data is using the experimental design to install fixed and rotating solar panels according to the sun and collect data by measuring the electricity produced from fixed and rotating solar panels. At the same time. The results of the research found that the installation of solar panels rotating according to the sun can produce electricity up to 45.190KWh in a period of 9 months and the fixed mode is 28.157KWh in a period of 9 months (difference in 60.49% of obtained energy). Therefore, the sun tracking system should be a practical system according to the amount of required energy consumption of the village.